Taxiway Pavement Evaluation to Support the Operational of Terminal 2 Juanda Airport - Istiar Istiar; Indrasurya B Mochtar; Wahju Herijanto; Catur Arif Prastyanto (IPTEK Journal of Proceedings Series, 2017)
The movement of aircraft and passengers at Juanda international airport was increasing each year. Juanda airport airside infrastructure was almost reaching the maximum capacity. So that, PT. Angkasa Pura I as the operator of Juanda airport planned to revitalize the Juanda airport terminal that located on the south side. This terminal was not already 8 years operating. The infrastructure to be evaluated was the strength of taxiway pavement.Juanda airport taxiway pavement evaluated by using software COMFAA. Data input into the software COMFAA was the existing pavement structure and movement of the aircraft that will use the terminal that in the south side of Juanda airport. The results showed that the existing taxiway pavement structure was able to hold the load of aircraft movements over 20 years. So that, to prepare a taxiway pavement in the south side of Juanda airport, PT. Angkasa Pura I need only overlay the existing taxiway pavement.